IMPLEMENTATION OF POSITIVE LEGISLATURE OF THE CONSTITUTIONAL COURT IN ELECTION LAWS AS AN ANTICIPATION OF FAMILY INTEREST CONFLICTS - Fadilah, Fatma; Rahmawati , Adinda Rizki (Journal Social Sciences and Humanioran Review, 2024)
The Constitutional Court is one of the institutions in Indonesia, as a democratic country where equality is in the hands of the people and elections are held directly, publicly, freely, secretly, honestly and fairly every five years. Law number 7 of 2017 concerning elections regulates election participants as subjects in the democratic process, to ensure that elections are carried out with integrity and provide equal rights to every citizen. In this case, family involvement in this election is an effort to prevent nepotism and maintain integrity and fairness in the democratic process. This research has a problem formulation related to legal regulations regarding the president's participation in the presidential election campaign with family ties as well as the application of the positive legislature of the constitutional court in the election law to anticipate conflicts of family interest. This research uses normative juridical law. Limiting family involvement in elections through election laws is an important step to prevent nepotism and abuse of political power. The Constitutional Court plays an important role in ensuring compliance with the constitution and providing a clear interpretation of family conflicts of interest. Keyword: Constitutional Court, Family, Elections